POLA KOMUNIKASI SINGLE PARENT DALAM MEMBENTUK KARAKTER ANAK - Fitriawardhani, Tira; Nurany, Fierda (Publiciana, 2024)
This research is motivated by the phenomenon of high divorce rates in the city of Surabaya in 2023 reaching 2,805 cases which have an impact on the number of single parents of divorce, both lawsuit and talaq divorces. This figure is 10% higher than in 2022. To respond to this, researchers conducted a single parent communication study that aimed to shape the character of children. The purpose to be achieved in this study is to examine the communication patterns of single parents in shaping the character of children. This study used qualitative methods and was conducted on Surabaya residents with a sample of 10 single parents. This study observed family communication patterns that describe the relationship between parents and children in two ways: setting orientation and conversation orientation. The results showed that the form of conversation orientation is more widely used so that children can express all their feelings openly to these remaining parents. Authoritarian communication is strongly avoided and emphasizes democratic communication with children